Facial Recognition Technology in Policing: A National Survey of Public Support for This Technology and Privacy/Safety Concerns - Miethe, Terance D. (Crime & delinquency, 2025)
Using a national sample of U.S. adults, this study examines the level of public support for facial recognition technology (FRT) and its correlates across different policing activities. Multivariate analyses are conducted to assess how public support for FRT usage is influenced by individuals’ perceptions of its effectiveness in enhancing public safety, privacy concerns about its usage, and other attitudes (e.g., trust in police, worry about crime victimization). Both public safety and privacy beliefs are found to influence support for FRT usage, but the effects of privacy concerns also vary across different policing contexts (e.g., high-profile policing situations, “order-maintenance” policing) and the level of trust in police. These results are discussed in terms of their implications for future research and public policy on FRT usage.